Senile asthenia as a predictor of the severity of the perioperative period in elderly and senile patients - M. B. Danyliuk; S. M. Zavhorodnii; A. I. Rylov; M. A. Kubrak; I. V. Pertsov (Zaporozhye State Medical University, 2023)
The aim. To evaluate the effectiveness of the diagnosis of senile asthenia using the Edmonton Frail scale in emergency abdominal surgery and to determine its impact on the severity of the perioperative period. Materials and methods. The study included 81 patients with acute cholecystitis on the background of gallstone disease, who were assessed for senile asthenia using the Edmonton Frail scale. For the reliability of the obtained results, only patients who were urgently hospitalized to the surgical department with gynecology beds of the emergency hospital with clinical symptoms of acute cholecystitis were included. All patients received treatment in only one department and according to the standards and clinical protocols of this clinic. Based on the Edmonton Frail score, all patients were divided into two groups. The comparison group included 50 (61.7 %) patients who did not have senile asthenia. The main group included 31 (38.3 %) patients diagnosed with senile asthenia. Results. Surgical treatment in both groups was carried out on an urgent basis using total intravenous anesthesia with artificial lung ventilation. According to the type of surgical intervention in both groups, preference was given to minimally invasive methods. Laparoscopic cholecystectomy in the comparison group was performed in 49 (98.0 %) patients, and only one patient (2.0 %) was converted and operation continued from the mini-access. In the main group, all surgical interventions were performed by the laparoscopic method, U = 759.50, P = 0.8841. Analyzing the results of the duration parameters and the need for prolonged mechanical ventilation, it can be seen that it progressively increases in patients with asthenia: in the comparison group 61.50 (48.00; 75.00) minutes, and in the main 93.84 (60.00; 80.00), U = 513.50, P = 0.0112. Also, we noted that in patients with senile asthenia, the number of postoperative complications increases: in the comparison group, there were only 2 (4.0 %) postoperative complications, while in the main group - 7 (22.6 %), U = 556.00, Р = 0.0337. Summarizing the results, it can be seen that due to increase of the frequency of postoperative complications and increase of the need for prolonged artificial ventilation of the lungs, the length of hospital stay of patients with senile asthenia increased: in the comparison group it was 7.9 ± 2.2 days, and in the main group 9.7 ± 3.2 days, U = 530.50, P = 0.0177. Conclusions. In our opinion, the Edmonton Frail scale is effective in diagnosing the severity of senile asthenia in elderly and senile patients in emergency abdominal surgery due to its simplicity and speed of use. The overall severity of the condition, heart failure in patients with senile asthenia lead to increase in the duration of surgery and the total duration of artificial lung ventilation: in the comparison group 39.52 (30.00; 45.00) minutes, while in the main group 49.19 (35.00; 50.00) minutes, U = 482.50, P = 0.0046. The duration of mechanical ventilation also differed significantly, in the comparison group 61.50 (48.00; 75.00) minutes, and in the main - 93.84 (60.00; 80.00), U = 513.50, P = 0.0112. The severity of senile asthenia negatively affects the course of the perioperative period, the frequency of postoperative complications increases: 2 (4.0 %) patients in the comparison group, while in the main group of 7 (22.6 %) patients, U = 556.00, P = 0.0337 and, as a consequence, the duration of inpatient treatment increases: in the comparison group it was 7.9 ± 2.2 days, in the main - 9.7 ± 3.2, U = 530.50, P = 0.0177. Modification of the approaches to preoperative preparation and postoperative management of elderly and senile patients diagnosed with senile asthenia will reduce the frequency of postoperative complications and reduce the length of hospital stay.